1997
DOI: 10.1046/j.1365-2958.1997.3401716.x
|View full text |Cite
|
Sign up to set email alerts
|

Host‐cell cyclophilin is important for the intracellular replication of Leishmania major

Abstract: SummaryThe antiparasitic effects of cyclosporin A were examined in leishmanial infection by analysing the role of CsA-binding proteins (cyclophilins) in the host-parasite interaction. We hypothesized that the leishmanicidal effects of CsA on Leishmania major infected macrophages might be mediated through a cyclophilin of either the parasite or the host cell. Two cyclophilins (20 and 22 kDa) were purified from L. major parasites and N-terminally sequenced. Although enzyme activity of these cyclophilins was inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Moreover, comparable amounts of Cyp40 were present in total cell extracts of monocytes and EC as shown by use of a semiquantitative immunoblot. Using the different methods, a severalfold higher expression level for CypA than for Cyp40 was found in both cells, comparable with other human cell lines and tissues (23). These results indicate that the difference in binding to the CsA resin was possibly attributable to a difference in intracellular interactions of the Cyp from both cells, which are competitive to CsA binding.…”
Section: Effect Of Csa On Ppiase Activities In Monocytes and Ecsupporting
confidence: 63%
See 2 more Smart Citations
“…Moreover, comparable amounts of Cyp40 were present in total cell extracts of monocytes and EC as shown by use of a semiquantitative immunoblot. Using the different methods, a severalfold higher expression level for CypA than for Cyp40 was found in both cells, comparable with other human cell lines and tissues (23). These results indicate that the difference in binding to the CsA resin was possibly attributable to a difference in intracellular interactions of the Cyp from both cells, which are competitive to CsA binding.…”
Section: Effect Of Csa On Ppiase Activities In Monocytes and Ecsupporting
confidence: 63%
“…The RII peptide (DLDVPIPGRFDRRSVAAE; Biomol, Hamburg, Germany) was labeled to ϳ600 cpm/pmol and purified on a RP-C2 clean up extraction column (Amchro, Sulzbach, Germany) as previously described (23). The peptide was eluted with 80% acetonitrile and freeze-dried, and reconstituted samples were stored in deionized water at Ϫ80°C.…”
Section: Cn Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that the mammalian host cell CyPA seems to be involved in the intracellular parasite's replication cycle of L. major parasites, as CyPA siRNA interference or CsA reduced the parasite burden [134]. Some of the small cyclophilins from Plasmodium falciparum and Toxoplasma gondii (TgCyP18) have similar inhibitory profiles as those established for the hCyPA (Table 3) [124,[126][127][128][129].…”
Section: Cyclophilins Intra-cellular Signaling and Development Of Camentioning
confidence: 83%
“…The biological role of host CyPs is more intriguing in a number of host-pathogen interactions (41). CyPs are specific targets for the CsA-mediated attenuation of a variety of parasitic infections, including leishmaniasis, malaria and toxoplasmosis (42). Interestingly, human CyPA promotes HIV-1 infectivity by forming a stable complex with the capsid protein in HIV-1 virions and promoting viral uncoating (30).…”
Section: Discussionmentioning
confidence: 99%